Pengaruh Kualitas Kontrol Internal dan Kepatuhan terhadap Standar terhadap Efektivitas Audit Sistem Informasi pada Perusahaan PT XYZ - Nunung Trimayanti; Joy Nashar Utamajaya (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2024)
The study aims to analyze the influence of internal control quality (X1) and compliance with standards (X2) on the effectiveness of information system audits (Y) in PT XYZ, a financial services company. The research adopts a quantitative approach with data collected through surveys and analyzed using multiple regression. Findings reveal that both internal control quality and compliance with standards significantly impact the effectiveness of information system audits, highlighting the importance of adherence to established frameworks such as COBIT 5. This research contributes to improved audit practices in similar organizational contexts.